Frequency of MRI Low Signal Intensity in the Buccal Fat of Fetuses and Speculation as to What It May Reflect - Shyam Sunder B. Venkatakrishna; Marcelo S. Takahashi; Juan S. Calle-Toro; Sean Schoeman; Juan Sebastian Martin Saavedra; Dana Alkhulaifat; Suraj D. Serai; Savvas Andronikou (MDPI AG, 2024)
Purpose: We aimed to characterize the fetal buccal fat pad (BFP) on magnetic resonance imaging (MRI) to determine the frequency and types of sequences on which the BFP demonstrates low signal intensity and determine any possible correlation with timing of the MRI during fetal development. Materials and Methods: A retrospective review of all fetal MR studies was performed, and a pediatric radiologist blinded to the referring and final fetal diagnosis as well as outcome evaluated the included cases. A positive buccal fat pad sign (BFS) was recorded as present if a round, symmetric, and bilateral area was seen in the submalar region of the face with the following signal characteristics: T1 hyperintensity, low signal on echo planar imaging (EPI), low signal on true fast imaging with steady-state free precession (TRUFI), and with restriction on diffusion-weighted imaging (DWI). Results: A total of one hundred sixty-seven (167) fetal MRI studies: one hundred fourteen (114) body (68%) and fifty-three (53) neuro (32%) scans were reviewed during the study period. The BFS was most commonly seen on EPI (63%) and TRUFI (49%) sequences. Substantial agreement between TRUFI and EPI (κ = 0.68; p < 0.01); moderate agreement between TRUFI and T1 (κ = 0.53; p < 0.01) as well as T1 and EPI (κ = 0.53; p < 0.01), and fair agreement between EPI and Diffusion (κ = 0.28; p < 0.01) was observed. The median gestational age (GA) was 24 weeks (IQR 22-30 weeks). The fetuses with a positive BFS were significantly older (mean GA of 27 weeks or higher) than those without, for each sequence. Conclusions: The focal low signal in the fetal buccal fat pad, termed the fetal BFS, is a commonly encountered normal finding in the majority of fetal MRI scans on TRUFI and EPI sequences. This finding may be related to the presence and development of brown adipose tissue in the buccal fat pad resulting in T2* effects, but further studies are needed in order to confirm this. Further work can incorporate any of the sensitive sequences demonstrating low signal in brown adipose tissue to map its distribution and development in the fetus and beyond.